Pesan Moralis Dalam Pendekatan Semiotika Lagu Mungkin Hari Ini Esok Atau Nanti Karya Anneth Delliecia - Erwin Setyawan; Yohanes Probo Sasongko (Jurnal Bahasa, Sastra, dan Budaya, 2022)
In language we find messages stored in it. This message presents its own comprehensive understanding. In Anneth's song with the title Maybe today, tomorrow or later, it tells about moral actions that are wrapped in hostility. Through this song, the message that is about to be conveyed in the current pandemic situation and conditions, implies meaningfully how we see and understand the existence of separate messages that are present in each object that is represented in depth. The contexts regarding the clips and clips taken are understood as separate messages that have moral values. Each context that is taken in the meaning process is wrapped in Roland Barthes' semiotic study which later gives color to be able to see and approach the meaning carried. In the analytical knife of the study of connotations, denotations and symbols, giving a comprehensive meaning can be drawn so close to the reality that exists in our society. Language becomes a priority in itself when looking at the whole of culture, social action, the study of morality which as a whole is summarized in communication and human culture. Keywords: Connotation 1; Denotation 2; Symbol 3